The Role of Spirituality in the Behavior of Sharia Bank Mobile Banking: Evidence from Indonesia - Inayah, Nur; Agriyanto, Ratno; Warno, W (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
The purpose of this research is to examine the behavior of sharia bank customers in using mobile banking (using a modified Technology Acceptance Model) with additional spiritual variables. The research population is about one hundred customers of sharia bank in Indonesia. The results of this study indicate that: (1) perceived ease has a positive effect on the attitude of using mobile banking through the use of perceptions, (2) the perception of benefits has a positive effect on the attitude of using mobile banking, (3) expediency has a positive effect on the behavioral interest in using mobile banking, (4) behavioral interest has a positive effect on mobile banking use, and (5) spiritual motivation has a positive effect on mobile banking use.